Technology and uses of liquid hydrogen - Scott, Russell B. (Russell Burton), 1902-; Denton, William Havelock; Nicholls, Cyril Minchin, 1914- (1964)
Technology and Uses of Liquid Hydrogen deals with the technological aspects and applications of liquid hydrogen. Topics covered include the process of producing hydrogen gas for liquefaction; thermal insulation, storage, transportation, and transfer of liquid hydrogen; liquid hydrogen engines and bubble chambers; and safety in the use of liquid hydrogen. The uses of liquid hydrogen for the production of cold neutrons inside a nuclear reactor are also discussed. This book is comprised of 11 chapters and begins with a little background, history, and statistics on the technology and uses of liqui.